Size specific energy (SSE) - Energy required to generate minus 75 micron material - Ballantyne, Grant; Peukert, Wolfgang; Powell, Malcolm (International Journal of Mineral Processing, 2015)
This paper explores the relationship between energy and the generation of minus 75 micron material. Rittinger's law of comminution states that the energy input is proportional to the generation of new surface area. An accurate and consistent measurement of surface area, applicable across multiple size ranges, is required to apply this practically. The amount of new - 75 μm material generated has previously been proposed as a proxy for surface area. This has been demonstrated to some extent on a range of different laboratory equipment, but not in a manner suited to equipment-independent ore characterisation. To this end the JK Rotary Breakage Tester (JKRBT) and Schönert breakage device have been used to measure the progressive production of fines from cumulative single impacts starting with 37.5 mm particles down to 250 μm. As per expectation, the generation of - 75 μm material was found to be proportional to the specific energy, but there was a secondary influence of size. A model was developed to describe the breakage and it was found that the standard t relationship could be used to effectively calculate the size specific energy. Measuring the intrinsic competence of an ore in this way can then be used to assess the energy efficiency of full-scale mills in relation to a lab scale test. It is envisaged that this relationship also has the potential to be used in the design of new comminution circuits. The methodology and the results from its application are presented for discussion and revie
Keywords: Benchmarking; Comminution; Efficiency; Energy